Community Foundations How To Series : Getting Started with a Community Foundation - Mesik, Juraj (World Bank, Washington, DC, 2012)
Community foundations are locally based grant making foundations that mobilize local philanthropic contributions to support variety of development projects. They are becoming increasingly important in mobilizing local resources and development expertise. These foundations play a particularly valuable role in assisting local development, strengthening resourcefulness and capacities, attracting new resources and cultivating philanthropy from local donors for community-based and Community-Driven Development (CDD). This note provides guidance to those considering community foundations as an element of a larger CDD or Social Investment Fund (SIF) project.